An outbreak of lymphocystis disease virus infection in cultured juvenile John's snapper (Lutjanus johnii) in Malaysia - Nurliyana, M. (Elsevier, 2023)
This study reports an outbreak of lymphocystis disease virus infection in cultured juvenile John's snapper (Lutjanus johnii) in Malaysia. In mid-January 2021, approximately 19,000 juvenile John's snapper exhibited signs of lethargy and isolating themselves from the schooling group, developed lymphocysts all over the body and fins, and died. The outbreak started at day 3 after the introduction of fish into the hatchery, and the severity of the disease was observed between day 7 and 14, resulting in 53% mortality. No bacteria was isolated, while a low prevalence of protozoan parasite was observed at 5% of fish samples. Histopathology examination revealed focal nodular dermal fibroblast hypertrophy with karyomegaly and hyaline capsule formation. Basophilic intracytoplasmic inclusions were observed in the diseased fish. PCR and sequence analyses revealed that all affected fish were positive to lymphocystis disease virus (LCDV), which was absent from the clinically healthy fish. Phylogenetic analysis revealed that the isolates from this outbreak were from the cluster of LCDV genotype 2. This paper reports the first documentation of LCDV infection in cultured John's snapper in Malaysia. Farmers and authorities should beware of the impacts LCDV infection, as it can cause high mortality and economic losses in cultured fish.